Retention of gross and clinical anatomy knowledge among medical graduates in Sudan: a comparative study - Mie Saeed; Lina Ahmed; Eltayeb AbdAlla; Zinab Alatawi; Amirah M. Alhowiti; Tasneem S. A. Elmahdi; Safaa Mohammed; Amal Elhag (BMC Medical Education)
Abstract Background Retaining anatomical knowledge is crucial for safe and effective medical practice, yet many medical graduates struggle to apply this knowledge in clinical settings over time. This study aimed to evaluate and compare the retention of gross anatomy and clinical anatomy knowledge among medical graduates in Sudan. Methods A cross-sectional study was conducted in a sample of 385 medical graduates from various Sudanese universities, estimated using the Cochrane formula. The participants completed a self-administered questionnaire assessing their knowledge of gross and clinical anatomy, as well as demographic and educational factors. The data were analyzed via descriptive statistics, paired t-tests, and ANOVA. Results Clinical anatomy knowledge was significantly better retained (mean score: 68.39%) than gross anatomy knowledge was (mean score: 45.35%). The retention of gross anatomy is influenced by academic background, with integrated and hybrid learning approaches showing better outcomes than traditional methods do. In contrast, clinical anatomy retention was more consistent across demographic factors but varied by speciality, with emergency medicine, general practice, surgery and radiology showing the highest retention levels. Conclusion Clinical anatomy is retained more effectively due to its frequent application in practice, whereas gross anatomy requires greater integration with clinical relevance to enhance retention. The study recommends medical curricula that merge gross and clinical anatomy through active learning strategies and continuous education to improve long-term retention and clinical competency.